Rural Electrification in Rwanda – An Impact Assessment Using Matching Techniques - Gunther Bensch; Jochen Kluve; Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Rural electrification is believed to contribute to the achievement of the Millennium Development Goals (MDGs) via various channels. In this paper, we investigate the impacts of electrification on the household's lighting usage, home studying, energy expenditures and income. We use household data that we collected in rural Rwanda in villages with and without access to mini-grids. To account for self-selection processes in the connection decision we use households from the electrified villages to estimate the probability to connect for all households - including those in the non-electrified villages. Based on these propensity scores we identify counterfactual households to determine the impacts of electrification on the outcome indicators. We find some indication for positive effects on home studying and income, but particularly on lighting usage. We conclude by highlighting the potentially profound changes in social life of rural people induced by improved lighting and call for research on impacts beyond the MDGs.
Keywords: O12; O13; O18; O22; 330; rural electrification; ex-ante impact assessment; poverty; matching